2018
DOI: 10.1371/journal.ppat.1006987
|View full text |Cite
|
Sign up to set email alerts
|

HIV-specific Fc effector function early in infection predicts the development of broadly neutralizing antibodies

Abstract: While the induction of broadly neutralizing antibodies (bNAbs) is a major goal of HIV vaccination strategies, there is mounting evidence to suggest that antibodies with Fc effector function also contribute to protection against HIV infection. Here we investigated Fc effector functionality of HIV-specific IgG plasma antibodies over 3 years of infection in 23 individuals, 13 of whom developed bNAbs. Antibody-dependent cellular phagocytosis (ADCP), complement deposition (ADCD), cellular cytotoxicity (ADCC) and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 105 publications
9
67
1
Order By: Relevance
“…The association of FcγRIIa binding with HIV-1 risk also remained significant in the IgA interaction model (OR = 0.405 [IgA -], P = 0.001; OR = 0.682 [IgA + ], P = 0.002) with the interaction P value being 0.200. Env IgG3 breadth is a weight-systemic HIV-1 infection, including clearance of virions that may decrease the number of functionally infectious virions to infect new cells and phagocytosis or trogocytosis of infected cells (54,55) that may limit their capacity to produce and spread new virions. Although our analysis showed no impact from IgG3, timing of exposure may be important to any impact on VL due to the rapid decline of Env IgG3 following vaccination (47).…”
Section: Volume 129 Number 11 November 2019mentioning
confidence: 99%
“…The association of FcγRIIa binding with HIV-1 risk also remained significant in the IgA interaction model (OR = 0.405 [IgA -], P = 0.001; OR = 0.682 [IgA + ], P = 0.002) with the interaction P value being 0.200. Env IgG3 breadth is a weight-systemic HIV-1 infection, including clearance of virions that may decrease the number of functionally infectious virions to infect new cells and phagocytosis or trogocytosis of infected cells (54,55) that may limit their capacity to produce and spread new virions. Although our analysis showed no impact from IgG3, timing of exposure may be important to any impact on VL due to the rapid decline of Env IgG3 following vaccination (47).…”
Section: Volume 129 Number 11 November 2019mentioning
confidence: 99%
“…This protection may be particularly efficient when several Fc-mediated activities are combined (158). Fc polyfunctionality increases over time following HIV infection and has recently been correlated with the further induction of neutralizing activity (195).…”
Section: Strategies To Induce Fc-mediated Antibody Functions By Vaccimentioning
confidence: 99%
“…ADCC responses to Env have been associated with improved clinical outcomes and places mutation pressure on HIV-1 virus (196,199,(201)(202)(203). While historically HIV studies have focused upon NK cell mediated ADCC, recent research has demonstrated the importance of other Fc functions mediated by neutrophils, macrophages, monocytes, and complement activation (204,205), such that polyfunctional antibody responses may be beneficial (172,206,207). Through the strong engagement of these particular Fc receptors in HIV infection, cells are activated resulting in downstream release of inflammatory cytokines and cytotoxic granules.…”
Section: Antibody Function In Hiv-1mentioning
confidence: 99%